Syzygium namborense (Myrtaceae), a new species from Assam, India - Dey, Debolina; Sarma, Jatindra; Devi, Nilakshee (Phytotaxa, 2022)
Syzygium namborense is described and illustrated as a new species from the Nambor Reserve Forest, Assam, India. It resembles Syzygium nervosum in having glabrous, chartaceous and aromatic leaves, paniculate inflorescences with second order branching, calyptrate flowers, numerous stamens and equal number of petals in the calyptra but differs from it in having more compressed branchlets with shorter nodes and greater number of leaves, shorter acumen, strictly elliptic leaves with acuminate apex and cuneate base, greater number of lateral veins, intramarginal vein uniform along the blade, sessile yellowish white flowers with obconical hypanthium and a higher number of ovules per locule.